2018
DOI: 10.1155/2018/9342326
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Polyoxometalates with Different Structures

Abstract: A new inorganic-organic hybrid compound, [{Cu(phen)2}2(H4W12O40)], was synthesized, and its crystal structure was determined. The Keggin anion H4W12O40 4− was grafted with two coordination units {Cu(phen)2}, forming an electrically neutral molecule. The antibacterial activity of several polyoxometalate compounds with different anionic structures including the new compound was studied. The results show that the compound 1 can inhibit the growth of Enterococcus faecalis FA2 strains and that antibacterial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…For a long time, polyoxometalates have been favored by researchers because of their remarkable anti-bacterial properties, which are promising alternatives to the commercial anti-bacterial agents [ 18 , 54 , 55 ]. In this work, an anti-bacterial film was prepared by incorporating the Wells-Dawson polyoxometalate into the κ-carrageenan matrix using the tape-casting method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, polyoxometalates have been favored by researchers because of their remarkable anti-bacterial properties, which are promising alternatives to the commercial anti-bacterial agents [ 18 , 54 , 55 ]. In this work, an anti-bacterial film was prepared by incorporating the Wells-Dawson polyoxometalate into the κ-carrageenan matrix using the tape-casting method.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ratio of center atoms to the hetero atoms, the most prominent and commonly used polyoxometalates can be divided into following types: Wells-Dawson, Keggin, Anderson, Waugh, Silverton, Lindqvist, Weakley, Strandberg, Finke, and Preyssle [ 14 ]. The decades of polyoxometalates research have revealed their great antimicrobial potential [ 15 , 16 , 17 , 18 ]. Particularly, Wells-Dawson and Keggin polyoxometalates were found to be most potent in terms of sensitizing methicillin-resistant S. aureus strains SR3605 and ATCC43300 among 76 tested POMs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, the antimicrobial activity was also reported, which is of great significance in the fight against drug-resistant bacteria. 22,23 There is also the effect of insulin mimicking to control diabetes, 24 as well as Alzheimer's disease. 25 However, some disadvantages of pure inorganic POMs, such as high toxicity and long-term toxicity, limit their scope of clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…As reported and confirmed in the literature, the electrochemical method has a high potential for DNA damage detection and is an attractive alternative approach for damage detection that has recently received more attention compared to other methods [ 2 ]. Polyoxometallates (POMs) are metal oxide aggregates with a great diversity in their structure and composition [ 3 ]. Their unique inherent properties make them promising candidates for medicine, magnetism, materials science, optics, biotechnology, and environmental sensing [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%